2014
DOI: 10.1007/s00436-014-3891-z
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic activity of Artemisia annua L. extracts in vitro and the effect of an aqueous extract and artemisinin in sheep naturally infected with gastrointestinal nematodes

Abstract: There is no effective natural alternative control for gastrointestinal nematodes (GIN) of small ruminants, with Haemonchus contortus being the most economically important GIN. Despite frequent reports of multidrug-resistant GIN, there is no new commercial anthelmintic to substitute failing ones. Although trematocidal activity of artemisinin analogs has been reported in sheep, neither artemisinin nor its plant source (Artemisia annua) has been evaluated for anthelmintic activity in ruminants. This study evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Among them, plants from the genus Artemisia are a rich source of bioactive sesquiterpene lactones and have a long history related to parasite control [12]. Also, several Artemisia species are popularly used as anthelmintics, such as A. absinthium L., which is known as absinthe [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, plants from the genus Artemisia are a rich source of bioactive sesquiterpene lactones and have a long history related to parasite control [12]. Also, several Artemisia species are popularly used as anthelmintics, such as A. absinthium L., which is known as absinthe [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Also, several Artemisia species are popularly used as anthelmintics, such as A. absinthium L., which is known as absinthe [12, 13]. Previous studies have reported that A. absinthium L. presented activity against Fasciola hepatica [13] and Haemonchus contortus [14].…”
Section: Introductionmentioning
confidence: 99%
“…Maximum reduction (67.2%) in EPG was recorded on day 14 post treatment in sheep with mixed gastrointestinal nematode infection treated with A. brevifolia crude aqueous extract at 3 g/kg BW (Iqbal et al, 2004). Cala et al (2014) evaluated A. annua sodium bicarbonate extract (2 g/kg BW) and artemisinin (100 mg/kg BW) in naturally infected sheep. Artemisinin-treated and extract-treated sheep had non-significant EPG reductions of 28 and 19%, respectively, but this extract had no artemisinin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in a previous trial by our research group, naturally infected sheep treated with A. annua sodium bicarbonate extract (aqueous 0.1% sodium bicarbonate) in a single dose of 2 g/kg BW in 20 mL of soybean oil had non-significant EPG reduction (19%). However, the extract tested in vivo contained no artemisinin, but had high antioxidant capacity (Cala et al, 2014). Lack of artemisinin was expected due to the affinity of this substance to ethanolic solvents instead of aqueous.…”
Section: Introductionmentioning
confidence: 97%
“…Plants of genus Artemisia are known to possess anthelmintic and therapeutic effects . Quite a few species are already reported to possess anthelmintic properties such as Artemisia annua L. extracts (Cala et al, 2014). In Northern areas of Pakistan, the use of Artemisia based treatment is also common practice.…”
Section: Introductionmentioning
confidence: 99%